Identification of Factors Causing Learning Difficulties In The 11th Grade Students on Cell Material and Substance Transport - Windi Amelia; Heffi Alberida (Bioeducation Journal, 2022)
Learning difficulties are the condition of learners who are not studying properly and are unable to obtain the predetermined KKM scores. Learners are experiencing learning difficulties influenced by several factors. Factors that affect learning difficulties learners are internal factors and external factors. Learning difficulties are often found in learners in following the learning process. Cell and substance transport is one of the high school class XI materials in biology lessons. In replication of cell material and transport of class XI MIA substances in SMA Negeri 1 Lubuk Alung shows value below KKM. So, based on the understanding of learning difficulties above means the students of class XI MIA in SMA Negeri 1 Lubuk Alung experiencing learning difficulties because they are unable to meet the limits of KKM which has been determined. Therefore, the researcher wanted to identify the difficulties of studying students in grade XI SMA Negeri 1 Lubuk Alung on cell material and substance transport.The type of this research is descriptive research. The instruments used in this study are questionnaires and questions. Questionnaire given in the form of statements and soaalnya in the form of multiple choice. The population of this study is the students of class XI MIA SMA Negeri 1 Lubuk Alung consisting of 7 classes with the number 231 people. The sample of this study was 70 people taken 10 people per class. Based on the data analysis can be seen the absence of the value of learners are complete after being given a matter of understanding the concept of the concept of cell material and substance transport. For the results of questionnaires data obtained the percentage of factors that cause the learning difficulties of the most high learners are themselves by 54.62%, the next school by 50.6%, the community 39.63% and the last family 30.94%.